Brand Awareness Quality and Loyalty Separate Momoyo and Mixue: Kesadaran Merek, Kualitas, dan Loyalitas Membedakan Momoyo dan Mixue - Oktaviani, Adinda Putri Eka; Andarini, Sonja (Academia Open, 2026)
General Background: Brand equity is essential in competitive food and beverage franchise markets because consumers evaluate brands through awareness, association, perceived quality, and loyalty. Specific Background: Two ice cream and tea franchise brands in Surabaya were compared because preliminary survey findings showed unequal consumer preference and taste as the main product selection consideration. Knowledge Gap: Prior studies have discussed brand equity dimensions, yet comparative evidence on brand awareness, brand association, perceived quality, and brand loyalty in contemporary ice cream and tea franchise consumers remains limited. Aims: This study aimed to compare brand equity dimensions between two ice cream and tea franchise brands among consumers in Surabaya. Results: Using a quantitative comparative approach with 100 respondents and Independent Samples T-Test analysis, the findings show significant differences in brand awareness, perceived quality, and brand loyalty, each with a significance value of 0.000. Brand association showed no significant difference, with a significance value of 0.259. One brand was stronger in recognition, purchase, consistent quality, word of mouth, and repeat purchasing, while the other was stronger in recall, consumption, acceptable quality, consistent performance, and rejection of other brands. Novelty: This study compares four brand equity dimensions simultaneously in the ice cream and tea franchise context. Implications: The findings support brand strategy development based on differentiated awareness, quality perception, and loyalty indicators. Highlights: Association patterns were statistically similar between both brands. Consumer recognition and recall showed different competitive strengths. Repeat purchasing and recommendation behavior differed significantly. Keywords: Brand Awareness, Brand Association, Perceived Quality, Brand Loyalty